Assessing the timing of invasive intervention in NSTE-ACS: insights from a meta-analysis and sequential trial evaluation - Yang, Wei; Ge, Xiao-Zhen; Wang, Chong-Hui (Frontiers in Cardiovascular Medicine, 2025)
BackgroundInvasive approaches are commonly recommended for treating patients with non-ST-elevation acute coronary syndromes (NSTE-ACS) to lower the risk of death caused by myocardial infarction (MI). However, the timing for implementing relevant interventions remains challenging to be determined, largely due to poorly understanding of the long-term clinical outcomes.MethodsA meta analysis with trial sequential analysis (TSA) was conducted to evaluate the impact of timing on the outcomes of invasive interventions for NSTE-ACS patients. A comprehensive search of PubMed and EMBASE databases identified 14 randomized controlled trials (RCTs), encompassing 16 studies with a total of 9,436 patients, in which two trials have additional long-term follow-up studies. Based on the timing of catheterization, all studies were categorized into two groups: early intervention group (median intervention time <24 h; range from 0.5–9.3 h) and delayed intervention group (median intervention time ≥24 h; range from 18.3–86 h). Clinical outcomes were assessed for primary endpoints (all-cause death or MI) and secondary endpoints (recurrent ischemia, requiring cardiac revascularization or major bleeding) respectively.ResultsEarly intervention did not significantly reduce all-cause mortality or the incidence of MI compared with delayed intervention. The frequency of revascularization and major bleeding were also similar between the two groups. A significant reduction was observed for the incidence of recurrent ischemia in early intervention group. Further analyses confirmed those findings across both short-term follow-up (30 days) and mid-to-long-term follow-up (180 days to 5 years). TSA provided additional evidence supporting the protective benefit of early intervention for recurrent ischemia but not for others.ConclusionsFor patients with NSTE-ACS, early invasive treatment does not reduce all-cause mortality or incidence of MI but is associated with a lower frequency of recurrent ischemia.